Enhancing Industrial Wastewater Oil Removal Through Integrated Coagulation–Flocculation Pretreatment and Dissolved Air Flotation (DAF) - Yustia Wulandari Mirzayanti; Purwaningsih, Dian Yanuarita; Ni'am, Achmad Chusnun; Awaludin, Aditya Fikri (Journal of Research and Technology, 2024)
Oil content in the water that exceeds the threshold can pollute the environment if disposed of directly without waste treatment. This study conducted a case study of engineering waste treatment containing 1% oil using the Dissolve Air Flotation (DAF) method through coagulant and flocculant pre-treatment. The independent variable used in this study is pressure and residence time, where the pressure variable consists of 0.6, 0.8, 1, 1.2, and 1.4 bar, while the residence time variables comprised 5, 15, 30, 45, and 60 minutes. This study obtained the maximum pressure and residence time, namely at a pressure of 1.4 bar and a residence time of 60 minutes; the highest oil removal was 98.32%. Turbidity removal was 92.31% in 1% of engineering waste for engineering destruction.